SYMBOLIC ANALYSIS OF EDUCATIONAL LEADERSHIP IN CHARACTER BUILDING IN ELEMENTARY SCHOOLS - Yoyo Zakaria Ansori; Budi Febriyanto; Saepul Anwar; Agus Fakhruddin (Universitas Majalengka, 2024)
This study was motivated by the lack of research on value-based leadership. The purpose of this study was to analyze symbols in the form of language, gestures, speech, and signs by examining their meaning in depth. This study used a qualitative approach and a case study research method. The data collection techniques used were in-depth interviews, observation, and document study to understand the symbols conveyed. The results of the study at SDN Cicenang 1, Cigasong Subdistrict, Majalengka Regency, indicate that the symbols conveyed by the school principal and teachers are the values of family, cooperation, democracy, and vision. These are the messages intended to be conveyed for character development among students at the elementary school level. Symbolism serves as a direct instrument, thereby becoming a role model for those around them.